A strategic plan of the Bagsakan Tagum City public market's fruit and vegetable section - Trinidad, Rolieto T.; Soledad, Miguel D.; Durana, Annalee D. (Davao City School of Management, University of the Philippines Mindanao, 2007)
The proposed strategic plan of the Tagum City's fruit and vegetable section popularly known as the Bagsakan is based on an evaluation of its effectivity in relation to the twin functions it is expected to do; viz, as a service provider of the city government of Tagum and as a local source of revenue. Contained in this study are suggestions to improve on these areas of concern. This study intended to determine whether the Bagsakan has lived up to the changes of the times especially as it relates to the changing conditions of the vegetable industry. Knowledge of these conditions can open opportunities for business and add economic value to its stakeholders. This study was made through personal interviews with select representatives of the different stakeholders. Questionnaires were also made on certain issues affecting the Bagsakan, the cooperation of the market supervisors and the Economic Enterprise Manager were sought and was easily facilitated. The collaboration of the officials of the different associations was particularly helpful. Visits to the vegetable producing areas of Maragusan, Compostela and New Bataan, all of Compostela Valley Province, were made to determine major vegetable supply route. Secondary data about vegetable production were provided by the Provincial Agriculturists of Davao del Norte and Compostela Valley province. Other sources of data were availed of from the Vegetable Industry Council of Mindanao (VICSMIN) and Growth for Equity of Mindanao (GEM) program of Davao City. A great part of the study was made through actual ocular observation of activities at the Bagsakan where the actions occurs. The output of this study is a five-year strategic plan outlining the strategies and activities that will help accomplish the goals and objectives identified in the study. It will serve as guide for the direction of the Bagsakan to attain competitiveness. It is a recommendation to the proper authorities, suggesting ways in which the Bagsakan can develop. It will be a testimony that public service can attain customer satisfaction as well as become sustainable. In the light of the present emphasis of the national government to promote the Bagsakan and food terminals, the Bagsakan study becomes particularly important and relevant to the ? Kasaganaang Abot-Kaya: Bagsakan Center (2007)", a Department of Agriculture program in cooperation with the Local Government Units.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, December 2007.
Keywords: Strategic plan